The Logistics Conception of the Value Chain of Wood - Fróna, Dániel; Oláh, Judit; Harangi-Rákos, Mónika (International Journal of Engineering and Management Sciences, 2017)
The importance of the forest management and timber producing is highly determined by the value chain of timber. The forest management and timber producing can basically contribute to achieve the goals of the sustainable development as producing and processing the wood as a raw material. The relationship of the multifunctional forestry management as producing different scale of products and services results that changing a member of the chain might cause the total net alternation of the forestry system’s added value. The added value of the special areas of the appropriate and sustainable forest management is the infrastructural, recreational and touristic services.